2014
DOI: 10.1002/ca.22309
|View full text |Cite
|
Sign up to set email alerts
|

Special pattern of endochondral ossification in human laryngeal cartilages: X‐ray and light‐microscopic studies on thyroid cartilage

Abstract: Endochondral ossification is a process that also occurs in the skeleton of the larynx. Differences in the ossification mechanism in comparison to growth plates are not understood until now. To get deeper insights into this process, human thyroid cartilage was investigated by the use of X-rays and a series of light-microscopic stainings. A statistical analysis of mineralization was done by scanning areas of mineralized cartilage and of ossification. We detected a special mode of endochondral ossification which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…As testosterone substitution leads to vocal changes, 35 testosterone depletion may as well alter the voice. Furthermore, endochondral ossification takes place in the laryngeal cartilage, a process that occurs more distinctively in men between 41 and 60 years compared with age-matched women, as was shown by Claassen et al 39 This increases the tension on the vocal folds, which causes an increase in frequency. The same mechanism reduces the elasticity of the vocal folds.…”
Section: Agementioning
confidence: 84%
“…As testosterone substitution leads to vocal changes, 35 testosterone depletion may as well alter the voice. Furthermore, endochondral ossification takes place in the laryngeal cartilage, a process that occurs more distinctively in men between 41 and 60 years compared with age-matched women, as was shown by Claassen et al 39 This increases the tension on the vocal folds, which causes an increase in frequency. The same mechanism reduces the elasticity of the vocal folds.…”
Section: Agementioning
confidence: 84%
“…Thyroid cartilage consists of hyaline cartilage, which undergoes calcification and ossification as part of the aging process. Histochemical and light microscopic studies by Claassen et al have shown special mode of endochondral ossification in the thyroid cartilage . The ossification process takes place in the central cartilage layer that contains hypertrophic chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Vascularization of the cartilage canals brings the osteoblasts and chondroclasts to lay down osteoid matrix on the rims of mineralized cartilage. After mineralization of the osteoid matrix, the ossification process results in bone formation . Based on these histochemical and light microscopic studies, we know that the mineralization and ossification process begins earlier than puberty with the chondroid matrix changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations